Compartilhamento de postes no Brasil: Dois modelos microeconômicos para ajudar a entender a ocupaç\~ao clandestina - Lucas Gustavo Arango; Mauricio Benedeti Rosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This work is divided into two complementary parts. In the first part, we develop a partial equilibrium model, through which it is possible to analyze the influence of tariff modicity and the illegal occupation of poles on four agents: energy distributors, telecommunications operators, and energy and telecommunications customers. The results obtained show, for four simulated pricing scenarios, the impacts on economic efficiency and social welfare. In the second part, game theory was used to analyze pole sharing between energy distributors and telecommunications operators, in particular the illegal occupation of part of the operators. The simulations evaluated both an extreme scenario and also contexts in which players have adaptative behaviour.
10419/284896
Keywords: D04; D42; D46; D47; D61; K23; K32; L11; L12; L94; L96; 330; social welfare; infrastructure sharing; pole sharing; partial equilibrium; game theory; electrical; economic efficiency; incentives; public policy